PENGARUH TINGKAT PENGANGGURAN DAN INFLASI TERHADAP DAYA BELI MASYARAKAT KALIMANTAN BARAT - B61110002, ZARKASI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aimed to determine the effect of the unemployment rate and the inflation rate to purchasing power in West Kalimantan. The purchasing power of the public or the purchasing power per capita expenditure level views of the population from year to year. The data used in this study is the data from 2002 to 2011 were obtained from BPS publications province of West Kalimantan. Data analysis techniques used in this study is a quantitative technique for the purpose to see whether there is influence of the unemployment rate and the inflation rate to purchasing power of West Kalimantan. Quantitative data were analyzed using linear regression Regression.. The study results showed that the unemployment rate negatively siqnifikan partially (people) to the people's purchasing power. This suggests that if a person is not employed or unemployed it will affect the earnings. Inflation rate of significant negative effect partially (people) to the people's purchasing power. This suggests that if inflation rises then it will reduce the purchasing power but the effect is not siqnifikan. Simultaneously (together) a significant difference between the unemployment rate and the inflation rate of the purchasing power in est Kalimantan. Keywords: Purchasing Power Society, Unemployment Rate, Inflation Rate..